Puṇẽ yethīla Śake 1839 cyā Jyotishasammelanācā ahavāla (Jyotishasammelana va Pañcāṅgapravartana Kameṭī, 1918)
Proceedings of the Seminar on Hindu astrology, organised by Jyotishasammelana va Pañcāṅgapravartana Kameṭi.